(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Linguistic features of the lexicon of jewelry in Turkic languages include the study of how words related to jewelry are used in these languages, and features related to their cultural and historical aspects. By studying these features, we can understand the origins of jewelry-related words, their cultural significance, and their interactions with other languages. These features are detailed below in this article.